1989
DOI: 10.1111/j.1651-2227.1989.tb17938.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Developing Overweight in School Children as an Indicator of Psychosocial Stress

Abstract: From a cohort of 971 Swedish children followed up from birth through 15 years of age, all the children who had shown an increment in relative weight of more than 15% (measured weight in % of standard weight for height) between the ages of 7 and 10 years (group A, n = 25), 10 and 13 years (group B, n = 23), and 7 and 13 years (group C, n = 22) were selected for the present study. For each case a control matched for sex and relative weight at 7 (groups A and C) or 10 years (group B) was selected. The degree of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 10 publications
2
37
0
2
Order By: Relevance
“…6,7 Adolescents have been shown to use eating as a means of coping with stress. 25 Putting on weight, as well as the poor academic performance, in our grades 7 ± 9 group could possibly be the consequence of social environmental factors, for example, stress in school. The grades 3 ± 6 students, being younger, probably have other ways of dealing with the stress.…”
Section: Discussionmentioning
confidence: 82%
“…6,7 Adolescents have been shown to use eating as a means of coping with stress. 25 Putting on weight, as well as the poor academic performance, in our grades 7 ± 9 group could possibly be the consequence of social environmental factors, for example, stress in school. The grades 3 ± 6 students, being younger, probably have other ways of dealing with the stress.…”
Section: Discussionmentioning
confidence: 82%
“…There is little research on stress and weight gain in children, but stress seems to precede weight gain (4). A powerful risk factor for the development of obesity is parental neglect (5), which many investigators consider to be related to stress.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, stress precedes weight gain (1), particularly gains in visceral fat (2,3). There is less research on stress and weight gain in children, but research in children has shown stress precedes weight gain (4,5). Stress can influence obesity by stimulating energy intake (6), and children may use snacking as a stress coping mechanism (7).…”
Section: Introductionmentioning
confidence: 99%
“…Stress or anxiety is related to higher body weight, [18][19][20] particularly in women. 21 Stress-induced eating can trigger onset and relapses of obesity and increase preferences for high fat and/or sweet foods.…”
Section: Introductionmentioning
confidence: 99%